2018
DOI: 10.1111/febs.14464
|View full text |Cite
|
Sign up to set email alerts
|

DNA:RNA hybrids at telomeres – when it is better to be out of the (R) loop

Abstract: R-loops (RLs) are three-stranded nucleic acid structures that contain a DNA:RNA hybrid and a displaced DNA strand. Genomic regions with GC skew and a G-rich transcript are particularly prone to form RLs. RLs play important physiological roles in cells; however, when present at abnormally high levels, they may threaten genome stability. The perfect GC skew of telomeric repeats and the discovery of telomeric repeat-containing RNA (TERRA), a long noncoding transcript that consists of the G-rich telomeric sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 121 publications
0
41
0
1
Order By: Relevance
“…R-loops have also been detected in the telomere repeat elements of host organisms and www.nature.com/scientificreports www.nature.com/scientificreports/ have an essential role in telomere maintenance 34 . Similar to host genomes, herpesvirus TRs are essential for viral genome stability 38 . This raises the question whether herpesvirus R-loops serve the same function as host R-loops.…”
Section: R-loop Forming Sequences Are Predominant In Dsdna Virusesmentioning
confidence: 99%
“…R-loops have also been detected in the telomere repeat elements of host organisms and www.nature.com/scientificreports www.nature.com/scientificreports/ have an essential role in telomere maintenance 34 . Similar to host genomes, herpesvirus TRs are essential for viral genome stability 38 . This raises the question whether herpesvirus R-loops serve the same function as host R-loops.…”
Section: R-loop Forming Sequences Are Predominant In Dsdna Virusesmentioning
confidence: 99%
“…Recently, Sagie et al (2017) demonstrated that the majority of telomeric repeat-containing RNAs (TERRAs) are GC skew rich and thus able to form strong R-loops. The RNA:DNA hybrid formation in TERRA upregulated contexts, as described in ICF patients LCLs, might contribute to the maintenance of the abnormal open chromatin status at the telomeric regions involved in telomeres shortening ( Deng et al, 2010 ; Toubiana and Selig, 2018 ).…”
Section: Regulation Of Dnmt3b Recruitment To Genomic Targetsmentioning
confidence: 99%
“…However, when TERRA levels increase, as shown for ATRX-null cells, it enhances R-loop (RNA-DNA hybrid) formation and G4 DNA stabilization, each of which increase replication fork stalling and collapse that then induces homology directed repair (HDR) and TIFs (Nguyen et al, 2017). The regulation of R-loops has also been proposed for other proteins that interact with G4 DNA during replication and/or at telomeres (Zhou et al, 2014;Ribeiro de Almeida et al, 2018;Toubiana and Selig, 2018;Maffia et al, 2020). It should also be mentioned here that somatic ATRX mutations, and to a lesser extent H3.3 and DAXX mutations, are prevalent in cancers characterized by ALT (alternative lengthening of telomeres), a HDR mechanism to maintain telomere length that is normally suppressed by ATRX (Heaphy et al, 2011;Lovejoy et al, 2012;Schwartzentruber et al, 2012;Pickett and Reddel, 2015;Verma and Greenberg, 2016).…”
Section: Replication Stress Impairs Progenitor Expansion Resulting Inmentioning
confidence: 99%